FAHREDDiN RAzi'NiN VARLIK ANLAYlŞI - Bozkurt, Mustafa (Fırat University, 2009)
In this study, eminent muslim philosopher Fakhr al-Din al-Razi' s opinions with regard to existence is considered after making some general assessments on the concept of "existence" .. It is well known that Razi created his own way of understanding the things and put forth his unique opinions in various topics despite being affected by the ideas of the is!amic philosophers such as Avicenna andAl-Farabi at same points. Razi had an authentic standing in his opinions with regard to the defınition, scdpe and the types of existence. The main features of Razi's ideas upon existence are evaluated in order to make sound assessments about the ontological aspect of his thinking syst~_m_ ..
Fakhr al-Din ai-Razi's Understanding of Existence
Keywords: Religious Studies; Din Araştırmaları